Dampak dan Tantangan Penggunaan Telepon Genggam di Kalangan Anak Sekolah Dasar - Andriyana, Andriyana (Journal of Society and Development, 2023)
This study is motivated by the rapid development of information and communication technology, which has introduced various terms to clarify technological products, one of which is mobile phones, also known as gadgets. This research aims to identify and describe the practice of mobile phone usage in the daily lives of elementary school children and to evaluate its impact on them. The study employs a qualitative method with a descriptive approach to gain an understanding of mobile phone usage at SDN 2 Biromaru, Sigi Biromaru District, Sigi Regency. Data collection techniques included literature review and field research, which involved observation, interviews, and documentation. The number of informants in this study was eight, selected through purposive sampling. The results indicate that technological advancements have increasingly attracted attention, particularly among elementary school students. The use of mobile phones has spread across all age groups, including young children, who should have their usage strictly controlled. This is crucial to prevent cases of violence or the spread of inappropriate content that should not be accessible to children. Therefore, the role of teachers and parents is vital in monitoring mobile phone usage, both at school and at home. Although technology brings positive benefits, such as easy access to information, there are also negative impacts, including behavioral and moral changes that conflict with the prevailing societal norms.